Comparing the effects of continuous infusion of esmolol and ramosetron alone and in combination on nausea and vomiting after laparoscopic cholecystectomy: A prospective, randomized, double-blind study. Issue 35 (2nd September 2022) - Ji, Jae Young; Kim, Nan Seol; Seo, Yong Han; Jung, Ho Soon; Chun, Hea Rim; Park, Jin Soo; Choi, Jeong Soo; Ahn, Jae Min; Kim, Woo Jong
Abstract : Background: Postoperative nausea and vomiting (PONV) is a common complication of laparoscopic cholecystectomy. Although PONV is usually mild, severe thing can delay recovery and prolong hospitalization. We aimed to investigate the effects of ramosetron and esmolol, alone and in combination, on PONV, and pain. Methods: We enrolled 165 patients in their 20s to 50s who had an American Society of Anesthesiology physical status score of 1 or 2 and were scheduled to undergo laparoscopic cholecystectomy. They were randomly allocated into 3 groups: groups R, E, and E+R. Patients in group R received 0.3 mg of ramosetron following surgery. Those in group E were intravenously administered a bolus of esmolol (1.0 mg/kg) before endotracheal intubation. They were continuously infused with esmolol during the surgery to maintain their heart rate at 60 to 100 beats per minute and mean blood pressure at 60 to 100 mm Hg, followed by a bolus of esmolol (1.0 mg/kg) following surgery. Patients in group E+R were intravenously administered a bolus of esmolol (1.0 mg/kg) before endotracheal intubation, infused esmolol during surgery, and administered 0.3 mg of ramosetron and a bolus of esmolol (1.0 mg/kg) following surgery. We monitored the PONV stages (none, nausea, retching, and vomiting) and symptom severity in 3 postoperative stages (0–30 minutes, 30 minutes to 6 hours, and 6–24 hours), the latter by using the visual analog scale (VAS). We conducted an analysis of variance to compare VAS scores between groups. Results: Patients in groups E (mean ± standard deviation VAS score, 3.62 ± 1.00) and E+R (3.66 ± 0.71) exhibited less pain ( P < .05) until 30 minutes following surgery compared to group R (5.72 ± 1.41). More patients in group E (28/50, 56%) experienced nausea compared to those in groups R (15/50, 30%) and E+R (8/50, 16%) until 30 minutes after surgery ( P < .05). However, there were no differences in the severity of retching and vomiting between the groups in any of the phases ( P > .05). Conclusion: Despite reducing pain after laparoscopic cholecystectomy, esmolol did not prevent PONV, whether used alone or in combination with ramosetron.